2020
DOI: 10.1002/smi.2977
|View full text |Cite
|
Sign up to set email alerts
|

How does yoga reduce stress? A clinical trial testing psychological mechanisms

Abstract: Yoga interventions can reduce stress, but the mechanisms underlying that stress reduction remain largely unidentified. Understanding how yoga works is essential to optimizing interventions. The present study tested five potential psychosocial mechanisms (increased mindfulness, interoceptive awareness, spiritual well‐being, self‐compassion and self‐control) that have been proposed to explain yoga's impact on stress. Forty‐two participants (62% female; 64% White) in a yoga program for stress reduction completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…In addition to physiological mechanisms, psychological processes include increased mindfulness, interoceptive awareness, self-compassion, self-control and spiritual well-being [108]. These proposed mechanisms are concordant with our findings where participants described their perceptions of the program impact as increasing self and body awareness, finding a personal oasis, and a sense of calm and relaxation.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to physiological mechanisms, psychological processes include increased mindfulness, interoceptive awareness, self-compassion, self-control and spiritual well-being [108]. These proposed mechanisms are concordant with our findings where participants described their perceptions of the program impact as increasing self and body awareness, finding a personal oasis, and a sense of calm and relaxation.…”
Section: Discussionsupporting
confidence: 91%
“…Findings from other studies support the positive effect of (physical) yoga on psychological well-being and stress (Bhat et al, 2012 ; Gard et al, 2012 ; Gorvine et al, 2019 ). Conversely, some studies found no effect on stress (Quach et al, 2016 ; Park et al, 2020 ). Admittedly, the yoga interventions under investigation in these studies varied greatly, making it hard to draw reliable conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an observed relationship between belief in God and stress may be a function of the measure of stress used. The DASS-21 stress subscale reflects less the global psychological sense of being overwhelmed than the physiological arousal from stress (Park et al 2021). It may be the case that belief in God reduces one's likelihood of feeling overwhelmed but does not impact one's general physiological arousal, even though it has been shown to relate to the likelihood of reacting to acute provocation (Farias and Newheiser 2019).…”
Section: Discussionmentioning
confidence: 99%